2014
DOI: 10.1186/s13059-014-0491-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide profiling of mouse RNA secondary structures reveals key features of the mammalian transcriptome

Abstract: BackgroundThe understanding of RNA structure is a key feature toward the comprehension of RNA functions and mechanisms of action. In particular, non-coding RNAs are thought to exert their functions by specific secondary structures, but an efficient annotation on a large scale of these structures is still missing.ResultsBy using a novel high-throughput method, named chemical inference of RNA structures, CIRS-seq, that uses dimethyl sulfate, and N-cyclohexyl- N'-(2-morpholinoethyl)carbodiimide metho-p-toluenesul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 68 publications
4
88
0
Order By: Relevance
“…Ribosome profiling in yeast (86), coupled with a transcriptome-wide sliding window analysis of either in vivo or in vitro structure along transcripts (91), identified low structure in the first window as the strongest regulator of translational efficiency (defined as total amount of protein produced per mRNA), consistent with previous genome-wide in vitro (32,43,57) and in silico structural analyses (5,25,37). In vitro and in vivo structurome studies in systems as disparate as Arabidopsis (22), yeast (91,119), Drosophila, C. elegans (56), mouse and human cell lines (40,106,120), and E. coli (19) have revealed that low structure upstream of the translation start site in comparison with flanking regions is a conserved meta-property ( Table 2). Low structure is also typically observed near the stop codon in the eukaryotic systems examined to date (22,40,43,56,106) (Table 2).…”
Section: Stability and Degradationsupporting
confidence: 53%
See 1 more Smart Citation
“…Ribosome profiling in yeast (86), coupled with a transcriptome-wide sliding window analysis of either in vivo or in vitro structure along transcripts (91), identified low structure in the first window as the strongest regulator of translational efficiency (defined as total amount of protein produced per mRNA), consistent with previous genome-wide in vitro (32,43,57) and in silico structural analyses (5,25,37). In vitro and in vivo structurome studies in systems as disparate as Arabidopsis (22), yeast (91,119), Drosophila, C. elegans (56), mouse and human cell lines (40,106,120), and E. coli (19) have revealed that low structure upstream of the translation start site in comparison with flanking regions is a conserved meta-property ( Table 2). Low structure is also typically observed near the stop codon in the eukaryotic systems examined to date (22,40,43,56,106) (Table 2).…”
Section: Stability and Degradationsupporting
confidence: 53%
“…One robust meta-property of mRNA structuromes is a triplet repeat pattern of predicted structure and/or reactivity that is present along the coding sequences (CDSs) of mRNAs but absent from UTRs. This phenomenon is recurrent in structuromes in silico (95), in vitro (19,40,43,119), and in vivo (22,106) and has been observed in multiple organisms, including E. coli (19), yeast (43,119), Arabidopsis (22), and mouse (40,106) and human (120) cell lines. The underlying basis of the triplet repeat-whether completely inherent in sequence, imposed by experimental or cellular conditions that affect RNA folding and reactivity, and/or somehow emergent from biases in library construction-has yet to be resolved, nor is it known why natural selection may have favored such a pattern.…”
Section: Meta-properties Of Rna Structuromesmentioning
confidence: 99%
“…Global RNA structure-probing approaches have been used with yeast cells (13,15), Drosophila melanogaster and Caenorhabditis elegans (16), Arabidopsis thaliana (17)(18)(19), mouse (20)(21)(22), human cells (23,24), and, most recently, with Escherichia coli (25). We applied the parallel analysis of RNA structure (PARS) and experimentally determined single-and double-stranded regions in the Y. pseudotuberculosis YPIII transcriptome at three different temperatures.…”
mentioning
confidence: 99%
“…Our previous work has shown that the same RNAs that become kinetically trapped in stable misfolded structures during transcription in vitro rapidly adopt thermodynamically favored structures in vivo (Mahen et al 2005(Mahen et al , 2010. Results of whole-genome structure analyses and large-scale RNA folding studies have also revealed considerable differences between RNA folding outcomes in vivo, in vitro, and in silico (Ding et al 2014;Yang and Zhang 2014) and highlight the importance of RNA structural dynamics (Kertesz et al 2010;Underwood et al 2010;Lucks et al 2011;Li et al 2012;Wan et al 2012;Incarnato et al 2014;Rouskin et al 2014). Comparisons of RNAs designed to adopt specific alternative structures with precisely calibrated differences in thermodynamic stability suggest that a very narrow window of free energy limits conformational exchange (Mahen et al 2010).…”
Section: Introductionmentioning
confidence: 99%